Microbial fertilizer for improving maize yield, straw decomposition and soil microbiome structure - Xie, Xianjin; Tao, Hua; Li, Yanan; Feng, Xueying; Li, Ke; Zhang, Zhehui; Yan, Junying; Wang, Xiaolin (Frontiers in Microbiology, 2025)
Microbial fertilizers represent a promising strategy to sustainably produce crops by enhancing the biological function of soil and availability of nutrients. However, there is a lack of study on their performance across diverse agroecological zones. In this study, we conducted a 3-year, two-site field experiment to assess the effects of a composite microbial fertilizer (Bacillus subtilis and Trichoderma harzianum) on the yield of maize (Zea mays), soil properties, straw degradation, and composition of the microbial community. The results showed that the microbial fertilizer treatment (MF) increased the yield of maize by 11.4 and 6.9% in Qingfeng Country (QF) and Xun Country (Xun), China, respectively, compared to normal chemical fertilizer (CF). These gains coincided with an enhanced straw degradation rate (SDR; +8.4–8.6%) and a tendency toward higher available phosphorus (AP; +15.4–19.7%), alongside shifts in bacterial and fungal composition. High-throughput sequencing revealed that Proteobacteria, Actinobacteriota, Acidobacteriota, and Chloroflexi dominated the bacterial communities at both sites, whereas the fungal communities were mainly composed of Sordariomycetes, Dothideomycetes, and Eurotiomycetes—taxa whose abundances displayed pronounced site specificity. Application of the microbial fertilizer was associated with higher relative abundance of Acidobacteriota by 22.7% (QF) and 60.8% (Xun) and that of Sordariomycetes by 13.7% (QF) and 30.9% (Xun), underscoring its strong, selective impact on the dominant bacterial and fungal assemblages. These regional differences underscore the influence of site-specific microbial assemblages on the performance of fertilizer. Partial least squares path modeling supported a plausible pathway in which changes in community structure and straw decomposition are linked to improved soil nutrient status, which in turn predicted yield (β = 0.846, R2 = 0.715). Together, the field data indicate that microbial fertilizers may act through multi-step, microbiome-associated pathways, with success depending on compatibility with native microbial assemblages and environmental context.